Nephroprotective Effect of Vinpocetine against Vancomycin-induced Nephrotoxicity in Rats - Abdulameer, Hassanen Ayad; Al-Zubaidy, Adeeb Ahmed (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: The kidney is a vital organ for the body and is vulnerable to drug toxicity. For methicillin-resistant Staphylococcus aureus, vancomycin is the antibiotic of choice. It has been accompanied by nephrotoxicity, which restricts its use. Numerous studies have reported that nephrotoxicity was linked to oxidative stress and inflammatory response. Vinpocetine is a derivative of vincamine alkaloid used to treat some neurological disorders and has antioxidant and anti-inflammatory effects. The objective of the study: To evaluate the nephroprotective effect of vinpocetine against vancomycin-induced nephrotoxicity in rats. Methods: Twenty-four albino male rats were randomly selected and divided into three groups (n = 8): (1) Normal group: apparently healthy rats. (2) Induction group: treated with vancomycin (200mg/kg) twice daily intraperitoneally for 14 days. (3) Vinpocetine group: As the group (2) and treated with vinpocetine (2.5mg/kg) twice daily orally, an hour before vancomycin administration. Results: Vinpocetine group demonstrated a significant decrease in urea, creatinine, and cystatin C serum levels compared to the induction group. Also, it showed a significant reduction in the renal tissue level of malondialdehyde and a significant elevation in the renal tissue level of glutathione as compared to the induction group. Furthermore, the vinpocetine group showed a significant decrease in the renal tissue levels of tumour necrosis factor-alpha and neutrophil gelatinase-associated lipocalin. Histologically, all rats in vinpocetine group showed a significantly reduced level of renal tissue damage. Conclusion: The present study shows that vinpocetine exhibited nephroprotective due to its antioxidant and anti-inflammatory effects. Keywords: Nephrotoxicity, Oxidative stress, Vancomycin, Vinpocetine.